Children living with disabilities and mother’s labor supply in developing countries: evidence from Argentina - Carella, Laura Fernanda (2024)
A child’s disability increases childcare demands causing two opposing effects on the mother's labor supply: while some types of disability require additional time spent reducing labor supply, othersrequire additional expenses increasing labor supply. This paper studies the effect of a child's disability on mothers' labor supply using data from the 2019-20 IPUMS MICS of Argentina. Four measures of disability are used: children with a functional disability (based on Washington Group criteria); children with functional difficulties for seeing, hearing, or walking; children with difficulties in the remaining functional domains; and children with a disability certificate or pension. The results suggest that having a child with disability certificate or pension reduces a mother's probability of participating in the labor force. No significant effect is found for mothers of a child with a functional disability. However, this arises from two opposing effects: a negative effect on mother’s labor supply of children with difficulties for seeing, hearing, or walking and a positive effect on mothers of children with difficulties in the remaining functional domains. The evidence also shows heterogeneous effects depending on the mother’s education. The (dis)incentive to participate is present for non-graduated mothers, while the effect is not statistically significant for graduated ones.